2020
DOI: 10.1080/14737159.2020.1758067
|View full text |Cite
|
Sign up to set email alerts
|

A CNN-aided method to predict glaucoma progression using DARC (Detection of Apoptosing Retinal Cells)

Abstract: Objectives: A key objective in glaucoma is to identify those at risk of rapid progression and blindness. Recently, a novel first-in-man method for visualising apoptotic retinal cells called DARC (Detection-of-Apoptosing-Retinal-Cells) was reported. The aim was to develop an automatic CNNaided method of DARC spot detection to enable prediction of glaucoma progression. Methods: Anonymised DARC images were acquired from healthy control (n=40) and glaucoma (n=20) Phase 2 clinical trial subjects (ISRCTN10751859) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 51 publications
(38 reference statements)
0
44
0
Order By: Relevance
“…Using fluorescently labeled Annexin, Cordeiro et al have demonstrated the ability to visualize apoptosis of individual RGCs in experimental models of neurodegeneration and in humans with glaucoma 61. DARCs may be able to register early stages of RGC pathology, although it is not well established whether DARCs can detect changes in RNFL thickness reliably earlier than OCT62 ; however, recent published findings from the Phase 2 DARC trial demonstrate it to predict RNF loss by 18 months in glaucoma eyes 73.…”
mentioning
confidence: 99%
“…Using fluorescently labeled Annexin, Cordeiro et al have demonstrated the ability to visualize apoptosis of individual RGCs in experimental models of neurodegeneration and in humans with glaucoma 61. DARCs may be able to register early stages of RGC pathology, although it is not well established whether DARCs can detect changes in RNFL thickness reliably earlier than OCT62 ; however, recent published findings from the Phase 2 DARC trial demonstrate it to predict RNF loss by 18 months in glaucoma eyes 73.…”
mentioning
confidence: 99%
“…Moreover, the magnitude of SRF was related to that of the DARC count, and this is attributed to the mechanism by which DARC identifies an early endothelial angiogenic activity, as seen for the first time in vivo in a rabbit model of hVEGF-induced angiogenesis/leakage. This is the first time DARC technology has been reported in a disease other than glaucoma and suggests its broader applicability as a biomarker of retinal activity [ 17 ] [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For analysis of DARC images, the newly described and unmodified DARC CNN algorithm was used to identify DARC spots [ 17 ]. Briefly, the DARC CNN algorithm comprised training a CNN to classify spots from a control dataset which was initially identified using template matching and manually classified by five observers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in 2018, the US Food and Drug Administration (FDA) approved an AI medical imaging device to detect certain diabetes-related eye problems [33]. Recently, the Wellcome Trust found a research developing an AI-aided method to detect glaucoma progression using Detection of Apoptosing Retinal Cells (DARC) 18 months earlier than the current gold standard method [34].…”
Section: Vertical Integration: Provide Customized Value-added Servicesmentioning
confidence: 99%